Enhancing consumer loyalty through brand preference and brand conviction - Rizky Khotijatul Mahgfiroh; Herning Indriastuti (Faculty of Economics and Business Mulawarman University, 2022)
This study points to analyze and explain the Effect of Brand Preference and Brand Conviction on Consumer Loyalty of Excelso Multirasa Franchise in Samarinda City. The population in this study is the people of the city of Samarinda who are consumers of Cafe Excelso. The sampling technique in this study used a probability sampling technique with a simple random sampling methodwith a sample of 120 respondents. Data collection techniques used open and closed questionnaires. The analysis was carried out usingSPSS version 23. This research is quantitative. The results of this study indicate that: (1)Brand Preference positive and significant effect on Consumer Loyalty, (2) Brand Conviction positive and significant effect on Consumer Loyalty.